Act of March, 1886 (Published as "Notice"), in St. Mary's Beacon, Oct. 13, 1887 at 2. - (:unkn) unknown (My University, 1887)
Be it enacted by the General Assembly of Maryland, That from and after the passage of this Act it shall not be lawful for any person in St. Mary's county to carry on the days of election and primary election, within three hundred yards of the polls, secretly or otherwise, any gun, pistol, dirk, dirk-knife, razor, billy or bludgeon; and any person violating the provisions of this Act shall be deemed guilty of a misdemeanor, and on conviction thereof by the Circuit Court of St. Mary's county, having criminal jurisdiction thereof, or before any Justice of the Peace of said county shall be fined not less than ten nor more than fifty dollars for each offence, and on refusal or failure to pay said fine shall be committed to the jail of said county until the same is paid.
Keywords: SENSITIVE PLACES